Identifying factors associated with bicycle helmet use behavior among college students - Kakefuda, Itsumi, author; Stallones, Lorann, advisor (Colorado State University. Libraries, 2008)
Traditional college age students belong to age groups which are at high risk of bicycle-related traumatic brain injuries and are known to be less likely to wear bicycle helmets compared to with other age groups. The study aimed to examine behaviors, attitudes, subjective norms, past bicycle helmet use, bicycle-related injury, and risk perceptions with regard to bicycle helmet use among student bicycle riders at Colorado State University. The long-term goal for the research is to develop bicycle helmet promotion programs targeted at this high risk group. A questionnaire was developed based on the Health Belief Model and the Theory of Reasoned Action, with the Stages of Change Model serving as a tool to classify bicycle riders into groups in accordance with current bicycle helmet use behaviors and future intentions to use. A total of 315 responses were collected. The study included data from 199 students who used bicycles for commuting and for recreation in the 30 days preceding the date of survey. Among the student bicycle riders, 37% wore bicycle helmets every time for recreation; however only 9% used bicycle helmets for commuting. Differences in study variables among groups with different bicycle helmet use patterns were examined. Psychosocial factors associated with bicycle helmet use deferred between two bicycle use purposes, commuting and recreation. The analysis revealed that bicycle riders acknowledged the importance of bicycle helmet use in terms of traumatic brain injury prevention regardless of current bicycle helmet use and intentions to use helmets in the near future. However, bicycle helmet non-users and inconsistent users were less likely to think that they needed to wear bicycle helmets for short distance bicycle riding including commuting to school, compared to riders who wore bicycle helmets every time they rode. Implications of the study suggest changes in methods currently used in bicycle helmet research. The study provided important information for the development of interventions among college-aged students.
Keywords: bicycle helmet; college students; health psychology; helmet use; injury prevention; psychosocial models; traumatic brain injury; social psychology